Influence of TBAB on the Chemical Speciation of Copper(II) Binary Complexes with Biologically Important Ligands, L-Glutamine and Succinic Acid - Adhikamsetty, R. K.; Prasad, U. S. N.; Rao, V. S.; Kishore, P. L.; Rao, G. N. (Journal of Scientific Research, 2022)
Influence of tetrabutylammoniumbromide (TBAB) on the chemical speciation of binary complexes of copper (II) with biologically important ligands, L-glutamine, and succinic acid has been studied in varying concentrations (0.0-3.0 %, w/v) of TBAB-water mixtures using a Control Dynamics-APX 175E/C pH meter at an ionic strength of 0.16 mol dm-3 and temperature 303 K. The models for the species of these ligands are refined by using the computer programs SCPHD and MINIQUAD75. Copper(II) active forms are ML, ML2, and ML2H for succinic acid and ML2 and ML2H for L-glutamine. The variation of stability constants with % w/v TBAB is explained based on electrostatic and non-electrostatic forces. The formed species distribution with pH at different solvent compositions and equilibria of the species are reported in the present study. The plausible structures for refined species are also presented.